1997
DOI: 10.1148/radiology.205.3.9393517
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic thoracic aortic aneurysm: treatment with endovascular stent-grafts.

Abstract: Transluminal placement of endovascular stent-grafts is a technically feasible method for treatment of traumatic thoracic aortic aneurysm and may be an effective alternative to open-chest surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
166
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(172 citation statements)
references
References 0 publications
1
166
0
5
Order By: Relevance
“…Traumatic injury of the aorta is usually immediately fatal; 57%-94% of these patients die at the scene or in the emergency room (1,2). Furthermore, the mortality rate for patients with aortic rupture who survive until they reach the hospital is estimated to be 41%-50% (3).…”
Section: Resultsmentioning
confidence: 99%
“…Traumatic injury of the aorta is usually immediately fatal; 57%-94% of these patients die at the scene or in the emergency room (1,2). Furthermore, the mortality rate for patients with aortic rupture who survive until they reach the hospital is estimated to be 41%-50% (3).…”
Section: Resultsmentioning
confidence: 99%
“…The interval between the trauma and diagnosis used in the literature to differentiate acute and chronic traumatic aortic injuries is not clear, varying between 36 hours and 3 months. [7,8] The interval between the trauma and diagnosis of a pseudoaneurysm may change. In a group of 10 patients operated for traumatic thoracic aortic aneurysms, Buket et al [9] reported this period to be between 1 day and 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Both Semba et al 13 and Kato et al 14 have reported endovascular stent -graft treatment of acute traumatic rupture with low mortality and no neurologic complications. The good operative results in the present and other series 15,16 attest to the worth of considering this treatment as the first choice for BAI with severe associated complications.…”
Section: Discussionmentioning
confidence: 99%